Assessing fatigue in adult blood cancer patients : a 24-hour repeated cardiopulmonary exercise test in New Zealand (a pilot study) : a thesis presented in partial fulfilment of the requirements for the degree of a Masters in Health Science at Massey University, Manawatū, New Zealand - Fuller, Toby Christian (Massey University, 2025)
Purpose: Cancer-related fatigue is a persistent issue in long-term survival for cancer patients in remission. This study assessed the effects of cancer-related fatigue/post-exertional malaise in adult blood cancer patients aged 20-35 years of age. Methods: Five adult blood cancer (ABC) patients in remission and five healthy controls (HC) were recruited. Each participant completed a maximal incremental cycle exercise test on day one and again 24 hr later. Heart rate (HR), blood pressure (BP), rating of perceived exertion (RPE), oxygen consumption (VO 2), carbon dioxide production (VCO 2) and workload (WL) were recorded during the 24-hour repeated CPET. Data analysis investigated these responses at anaerobic threshold (AT) and peak work rate (PWR). Results: On day one, VO 2 at PWR were similar between both groups (ABC 38.62 +/- 16.21 ml.kg.min -1, HC 38.91 +/- 14.14 ml.kg.min -1), despite a difference in WL (ABC: 186 +/- 44.49 Watts; HC: 222 +/- 35.81 Watts). On day two, ABC saw a decrease in WL (165 +/- 45 Watts) alongside VO 2 (35.34 +/- 16.67 ml.kg.min -1) at PWR, despite no change in WL (D2: 222 +/- 38.83 Watts) and a slight increase in peak VO 2 for HC (40.19 +/- 14.61 ml.kg.min -1) at PWR. Across the two-day comparison, there was a significant decrease in VCO 2 (P=0.32), Time to completion of the test (P=0.17), WL (P=0.05), and HR (P=0.02) at PWR in ABL compared to no significant changes in HC. No significant changes were seen at AT in either group. On the second day, ABC could only increase HR to 87% +/- 6.84% of Max HR, compared to achieving 95.09% +/- 4.69% of Max HR on day one. Conclusion: These results highlight significant cancer-related fatigue/post-exertional malaise in adult blood cancer patients in remission. This fatigue will affect participants' emotional, social, and physical well-being and reduce their ability to lead everyday lives. This study forms an important stepping stone for how fatigue is assessed and exercise prescribed in cancer survivors.
Keywords: 420702 Exercise physiology